Automated Peak Harvesting of MALDI–MS spectra for high throughput proteomics. Issue 2 (2003) - Breen Breen, E. J. E. J.; Holstein Holstein, W. L. W. L.; Hopwood Hopwood, F. G. F. G.; Smith Smith, P. E. P. E.; Thomas Thomas, M. L. M. L.; Wilkins Wilkins, M. R. M. R.
Abstract : High throughput proteomics is realized not only by the use of automated hardware but also by the application of efficient, automated software routines to complex data. In this paper, we present the recent developments of our software tool Peak Harvester for the automatic harvesting of monoisotopic peaks from MALDI-TOF mass spectra of peptides. Peak Harvester uses advanced mathematical morphology to convert mass spectra into stick representations. Poisson modeling of theoretical isotopic distributions is then applied to derive the monoisotopic peptide mass from an isotopically resolved group of peaks. The accuracy of Peak Harvester is demonstrated via the analysis of peptide spectra from low concentrations of bovine serum albumin blotted onto PVDF membranes and of tryptic digested platelet proteins derived from human blood following two-dimensional gel electrophoresis. The results demonstrate the power of this software as it can accurately assign monoisotopic masses, including those from overlapping isotopic distributions, and picks masses as accurately as an experienced human operator. We have further developed Peak Harvester to include peak harvesting from MALDI-TOF Post Source Decay (PSD) experiments. Here we demonstrate the versatility of the software by both the analysis of PSD data from 2DE and the analysis of peptide mass spectra collected directly from tryptic digests on a PVDF membrane.